REPORTING OF REGIONAL HEAD ELECTION CAMPAIGN FUNDS IN 2018 PARIGI MOUTONG REGENCY ACCORDING TO COMMISSION REGULATIONS GENERAL ELECTION NUMBER 5 YEAR 2017 - Egar Mahesa; Muh. Akbar; Yusuf Hasmin (Program Pascasarjana Universitas Muhammadiyah Palu, 2023)
Regional head candidate pairs are obliged to report campaign funds in the form of LADK, LPSDK and LPPDK to the General Election Commission of Parigi Moutong Regency. After the report was received, the KPU ordered an audit team from the Public Accountant Office (KAP) to audit in order to adjust incoming and outgoing funds. This is done by the General Election Commission to increase the compliance of political parties and regional head candidates through outreach regarding campaign finance regulations. In addition, improving the facilities and infrastructure for reporting campaign funds and maximizing the application of sanctions for political parties and pairs of regional head candidates who commit campaign finance reporting violations that are not in accordance with applicable laws and regulations. Therefore, the KPU should be given the authority to carry out investigative audits of campaign funds owned by regional head candidate pairs and apply sanctions to those who report campaign funds not in accordance with the General Election Commission Regulations.